Mass spectrometry of metalloporphyrins. 2. Vapor pressure of cobalt, nickel, and copper octaethylporphyrinates - D. S. Lutokhina; G. S. Veryasov; A. V. Bakhtin; Yu. M. Kiselev (Тонкие химические технологии)
The volatility of cobalt, nickel, and copper octaethylporphyrinates was studied by the Knudsen method. Thermodynamical characteristics of sublimation of these compounds were obtained.